Pengaruh Ekstrak Ethanol dan N-Hexan Daun Serai (Cymbopogon citratus) Terhadap Larva Nyamuk Aedes aegypti - Gland Konay Octavianus; Abdul Chamid; Dheasy Herawati (Jurnal SainHealth, 2023)
Dengue hemorrhagic fever (DHF) is a disease transmitted by the bite of a female Aedes aegypti mosquito infected with the dengue virus. The essential oil contained in lemon grass has antioxidant activity and contains active compounds that are toxic as larvicides. The purpose of this study was to determine the effectiveness, and the effective concentration of the Ethanol and N-Hexan extracts of lemon grass (Cymbopogon ciratus) leaves. The research subjects were 300 instar III Aedes aegypti larvae containing 25 larvae at each concentration with each concentration group namely 30 ppm, 35 ppm, 40 ppm, 45 ppm, and 50 ppm, which were observed for 1 hour, 3 hours, 6 hours, and 24 hours. From the results of the ethanol extract of citronella leaves (Cymbopogon ciratus) using graded concentrations Aedes aegypti larvae can die at high concentrations of 50 ppm and can kill 14 Aedes aegypti larvae. Whereas in the N-Hexan extract of lemongrass leaves (Cymbopogon ciratus) using graded concentrations Aedes aegypti larvae can die at high concentrations of 50 ppm which can kill 11 Aedes aegypti larvae. Lemongrass leaves (Cymbopogon ciratus) are effectively used as natural larvicides. Effective concentrations are 35 ppm, 40 ppm, 45 ppm, 50 ppm for 24 hours.Â Keywords: Aedes aegypti, Dengue Hemorrhagic Fever, Lemongrass (Cymbopogon ciratus) leaves.